Wood ash on eucalyptus seedling production - Vieira, Cristiane Ramos; Weber, Oscarlina Lúcia dos Santos (Revista Ecologia e Nutrição Florestal - ENFLO, 2018)
The wood ash, although little used in the composition of substrates for seedlings production, can contain readily available nutrients and, therefore, increase the fertility conditions of the substrate. Because of it was carried out experiment in nursery in order to verify the combination of: soil, commercial substrate (Plantmax®) and plant ashes, more suitable for the production of Eucalyptus camaldulensis seedlings. The seedlings were grown in plastic tubetes with a capacity of 160 cm³ using seeds germinated in sand and vermiculite. When they reaching 15 cm of height, the plants were transplanted to the treatments: 100% soil; 75% soil + 25% ash; 75% Plantmax® + 25% ash; 50% soil + 50% ash; 50% Plantmax® + 50% ash; 50% soil + 25% Plantmax® + 25% ashes, arranged in a randomized design with 10 repetitions. The evaluation of the growth occurred 90 days after transplantation, with the measurement of shoot height, diameter collect, the leaf biomass, stem biomass, roots biomass and concentrations of nutrients in the leaves of seedlings. The combinations of substrates that provided the greatest growth of E. camaldulensis seedlings were 50% solo + 50% ash and 50% Plantmax® + 50% ash.